The Enduring Potential of Justified Hypernorms. Issue 3 (July 2019) - Scholz, Markus; de los Reyes, Gastón; Smith, N. Craig
ABSTRACT: The profound influence of Thomas Donaldson and Thomas Dunfee's integrative social contracts theory (ISCT) on the field of business ethics has been challenged by Andreas Scherer and Guido Palazzo's Habermasian approach, which has achieved prominence of late with articles that expressly question the defensibility of ISCT's hypernorms. This article builds on recent efforts by Donaldson and Scherer to bridge their accounts by providing discursive foundations to the hypernorms at the heart of the ISCT framework. Extending prior literature, we propose an ISCT* framework designed to retain ISCT's practical virtue of managerial guidance while answering the demands of Scherer and Palazzo's discursive account. By subscribing to a suitable portfolio of discursively justified hypernorms, we argue, companies unlock the valuable moral guidance of ISCT*, which says to treat these hypernorms as unequivocal outer bounds to the pursuit of business and as a starting point to tailor local norms through discursive stakeholder engagement.